The legal study on interfaith marriage in Bangladesh : issues and prospects for reform - Hassan, Kamrul (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2021)
Interfaith marriage is socially, religiously and legally contested and one of the most complicated issues in Bangladesh. This study focuses on the Special Marriage Act, 1872 and its practice in the current legal setting of Bangladesh. It examines the existing law on the current interfaith marriage practices and legal issues emanating from the existing law in Bangladesh. This study adopted a qualitative method which is a combination of the doctrinal and non-doctrinal research. For the doctrinal research method, it drew data from various legal writings, national laws, international laws, case law, etc. For the non-doctrinal research method, the study conducted in-depth semi-structured interviews to obtain data from various respondents in Bangladesh, namely, interfaith couples, social activists, religious experts, local police officers, special marriage registrars, judges, lawyers and academics. This study examined the benchmark with the Indian, Malaysian and Indonesian interfaith marriage laws and practices. The findings of this study demonstrate that the number of interfaith marriage-related problems is increasing in the current socio-religious and legal landscape. Similarly, it discovered that the existing provisions of the Special Marriage Act, 1872 are extremely inadequate to handle existing interfaith marriage disputes. It also shows that the court faces various difficulties in determining the disputants' rights and obligations. Lastly, it reveals that legal and judicial conflicts are created by the inadequacy of the existing law. The study, therefore, recommends by suggesting that there is a need to amend the Special Marriage Act, 1872 which is inadequate in the current legal setting. However, for a long term solution, the existing law needs to be abolished and replaced by the law governing Muslim and non-Muslims as regards the possibility of resolving conflicts between laws.